2017
DOI: 10.1136/bmjopen-2017-016392
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a UK community-based, eTherapy mental health service in Greater Manchester: repeated-measures and between-groups study of ‘Living Life to the Full Interactive’, ‘Sleepio’ and ‘Breaking Free Online’ at ‘Self Help Services’

Abstract: ObjectivesThere is increasing evidence to support the effectiveness of eTherapies for mental health, although limited data have been reported from community-based services. Therefore, this service evaluation reports on feasibility and outcomes from an eTherapy mental health service.Setting‘Self Help Services’, an Increasing Access to Psychological Therapies (IAPT) eTherapy service in Greater Manchester.Participants1068 service users referred to the service for secondary care for their mental health difficultie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 63 publications
2
29
0
Order By: Relevance
“…We found improvements in the PHQ-9 and WSAS scores, consistent with another IAPT study which showed that the use of the dCBTi platform resulted in improvements in the PHQ-9, GAD-7 and WSAS scores (Elison et al, 2017). dCBTi has been shown to be cost-effective in one study of guided dCBTi for insomnia to teachers, with a cost saving of US$418 achieved per patient for the employer (Thiart et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found improvements in the PHQ-9 and WSAS scores, consistent with another IAPT study which showed that the use of the dCBTi platform resulted in improvements in the PHQ-9, GAD-7 and WSAS scores (Elison et al, 2017). dCBTi has been shown to be cost-effective in one study of guided dCBTi for insomnia to teachers, with a cost saving of US$418 achieved per patient for the employer (Thiart et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Of the patients who had engaged sufficiently with dCBTi to be screened to be suitable for therapy, a further one-third had dropped out before therapy. Average drop-out rates have been estimated at 24.7% in a meta-analysis (Zachariae et al, 2016) and are similar to findings from a large IAPT cohort in the UK (Elison et al, 2017). dCBTi non-completers had lower baseline PSQI scores and higher sleep efficiency, which reflect better sleep quality when compared with dCBTi completers.…”
Section: Discussionsupporting
confidence: 73%
“…The effects sizes are typically in the moderate-to-large range. Additionally, in audits of clinical services, improvements in depression were equally seen [ 67 , 68 ], suggesting these effects hold in real-world, clinical settings. It has even been suggested that the effect of dCBT for insomnia is in the same range as CBT specifically aimed at treating depression [ 59 ].…”
Section: Evidence For Dcbt For Insomniamentioning
confidence: 99%
“…1 One such approach is the offer of internet-based or smartphone-based interventions within healthcare services. [1][2][3][4] In the UK, their potential is recognised in health policy documents such as England's National Health Service (NHS) Long-Term Plan (https:// www.longtermplan.nhs.uk/). The plan outlines an intention to work with the voluntary sector, developers and individuals in developing a range of apps to support mental health, with an aim to offer digitally enabled models of therapy for anxiety and depression across services by 2020.…”
mentioning
confidence: 99%
“…(2) IQR, interquartile range.Key factors for unlocking the potential of digital mental health technologies…”
mentioning
confidence: 99%